2019
DOI: 10.1007/s11605-018-3907-6
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT4 Receptor Agonist Prucalopride Stimulates Mucosal Growth and Enhances Carbohydrate Absorption in the Ileum of the Mouse

Abstract: Parenteral administration of the 5-HT4 receptor specific agonist, prucalopride, results in morphologic and functional changes in the murine small intestine that are most prominent in the distal small bowel. While further studies are necessary to delineate the mechanism, it is plausible that the effects are mediated by 5-HT4 receptors on enterocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…21 In the mouse ileum, systemic administration of prucalopride by osmotic pumps was shown to stimulate mucosal growth and increase carbohydrate absorption. 20 Furthermore, a recent study by Kashyap et al 35 identified gut microbiota-derived tryptamine as a ligand for the epithelial 5-HT 4 R, which induces accelerated whole gut transit and colonic secretion in mice, supporting the concept that the prokinetic actions of the 5-HT 4 R lie within the epithelium and not necessarily in the muscularis propria.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…21 In the mouse ileum, systemic administration of prucalopride by osmotic pumps was shown to stimulate mucosal growth and increase carbohydrate absorption. 20 Furthermore, a recent study by Kashyap et al 35 identified gut microbiota-derived tryptamine as a ligand for the epithelial 5-HT 4 R, which induces accelerated whole gut transit and colonic secretion in mice, supporting the concept that the prokinetic actions of the 5-HT 4 R lie within the epithelium and not necessarily in the muscularis propria.…”
Section: Discussionmentioning
confidence: 92%
“…In a study of potential protective effects of enema administration of 5‐HT 4 R agonists, we found that agonist treatment decreased the extent of colitis, and accelerated recovery from established colitis, in conjunction with increased epithelial proliferation, wound healing, and resistance to oxidative stress 21 . In the mouse ileum, systemic administration of prucalopride by osmotic pumps was shown to stimulate mucosal growth and increase carbohydrate absorption 20 . Furthermore, a recent study by Kashyap et al 35 identified gut microbiota‐derived tryptamine as a ligand for the epithelial 5‐HT 4 R, which induces accelerated whole gut transit and colonic secretion in mice, supporting the concept that the prokinetic actions of the 5‐HT 4 R lie within the epithelium and not necessarily in the muscularis propria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, together with evidence that treatment with prucalopride, a pharmacologic 5-HTR 4 agonist, increased small intestine morphometric and proliferative markers in mice, suggest that serotonin signaling causes intestinal epithelial cell proliferation both directly and via a cholinergic pathway. 38 The activity of 5-HTR 4 on other cell types supports its role in intestinal epithelial proliferation. For example, 5-HTR 4 on enteric neurons is implicated in neurogenesis through a pathway by which intracellular cAMP Q18 production activates proteins involved in cellular proliferation-namely protein kinase A and the extracellular-signal regulated kinase pathway.…”
Section: Q23mentioning
confidence: 96%
“…Citalopram, an SSRI, and prucalopride, a 5-HTR 4 agonist, have been shown to increase mucosal surface area and the absorptive capacity of the intestinal epithelium in mouse models. 38,61,63 In addition, citalopram treatment confers a protective effect to the intestinal epithelium in a mouse model of intestinal ischemia, with enhanced enterocyte renewal. 65 As mentioned previously, SSRI use has not been associated with increased rates of intestinal neoplasia, despite the evidence linking serotonin potentiation to enterocyte proliferation and colorectal cancer pathogenesis, and has in fact been shown to have therapeutic potential in reducing tumor viability in other malignancies.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%